(untitled) (The Pakistan Development Review, 2011)
This paper presents a theoretical model with micro-foundations that captures some important features of Pakistan‘s economy which have emerged in sixty-four years of its history. A comparison of Pakistan‘s economic performance during different regimes shows that macroeconomic fundamentals tend to show an improvement during the autocratic regimes as compared with those prevailing during democratic regimes. In particular, periods of autocratic regimes are typically characterised by low inflation, robust growth and low level of bureaucratic corruption due to better governance. In contrast, the economic performance during the democratic regimes has been observed to worsen with weak governance and high levels of corruption, high inflation due partly to reliance on seigniorage to finance public spending, and lacklustre growth. Using annual data from 1950 to 2011, computational modelling is carried out by applying Markov-Regime switching technique with maximum-likelihood procedures. The estimation results based on empirical modelling setup are supportive of the above stylised-facts and also confirm the implications of the theoretical model. JEL classifications: D73, E31, H60, O42 Keywords: Political Instability, Governance, Corruption, Inflation, Growth